Interleukin-10 -1082 G/A gene polymorphisms in Egyptian children with CAP: A case–control study. Issue 26 (June 2016) - Azab, Seham F.; Abdalhady, Mohamed A.; Elsaadany, Hosam F.; Elkomi, Mohamed A.; Elhindawy, Eman M.; Sarhan, Dina T.; Salam, Mohamed M.A.; Allah, Mayy A.N.; Emam, Ahmed A.; Noah, Maha A.; Abdelsalam, Nasser I.; Abdellatif, Sawsan H.; et al.
Abstract : Abstract: Community-acquired pneumonia (CAP) is one of the leading causes of death worldwide. Cytokines are involved in the pathogenesis of CAP. To date, only a few studies concerned the association of interleukin-10 (IL-10) gene polymorphisms with CAP. In this study, we aimed to investigate whether the -1082(G/A) polymorphism in the promoter region of the IL-10 gene is involved in susceptibility to and the outcome of CAP, and we also measured the serum level of IL-10 to assess its relation to such polymorphism. This was a case–control study included 100 patients with CAP, and matched with age, gender, and ethnicity of 100 healthy control children. IL-10 -1082(G/A) gene polymorphism was genotyped by polymerase chain reaction-restriction fragment length polymorphism, while the serum IL-10 levels were measured by ELISA method. Compared to the controls subjects, the frequencies of the IL-10 -1082 AA genotype and A allele were observed to be overrepresented in patients with CAP (51%; odds ratio [OR] = 2.8; 95% confidence interval [CI]: 1.5–5.3 for the AA genotype; P  < 0.01) and (70%; OR: 1.95; 95% CI: 1.27–3.00 for the A allele; P  < 0.01, respectively). We found that patients with the GG genotype had significantly higher serum IL-10 levels (46.7 ± 9.5 pg/mL) compared to those with AG genotype (21.8 ± 4.5 pg/mL) and AA genotype (11.5 ± 3.3 pg/mL); P  < 0.01, respectively. Our data revealed a significant positive association between the -1082 GG genotype and susceptibility to severe sepsis, acute respiratory failure, and hospital mortality (OR: 3.8; 95% CI: 1.3–11.2; P  < 0.01). We demonstrate for the first time, to the best of our knowledge, that IL-10 -1082 (G/A) gene polymorphism may contribute to susceptibility to CAP in Egyptian children. Moreover, we observed that the presence of a G allele or GG genotype at the -1082 position of the promoter region of the IL-10 gene constitute risk factors for developing severe sepsis, acute respiratory failure, and hospital mortality among patients with CAP.